Pengaruh Penerapan Teknik Relaksasi Otot Progresif Berbasis Musik Instrumental terhadap Gejala Stres Kerja pada Pegawai di Dinas Kesehatan Kabupaten Probolinggo - Barlian, Salwa Isna; Sulistyorini, Anita; Marji, Marji; Kurniawan, Agung (National Journal of Occupational Health and Safety, 2025)
Work stress symptoms are a condition where there is a mismatch between a person's condition and work demands, resulting in mental (psychological), physical, and behavioral disorders. Government employees are among those who are vulnerable to experiencing work stress symptoms. Based on preliminary study results, the Probolinggo Regency Health Office is one of the type A offices with a high workload, and several employees have been found to experience symptoms of work stress. The purpose of this study was to determine the effect of applying instrumental music-based progressive muscle relaxation techniques on work stress symptoms in employees at the Probolinggo Regency Health Office. The method used in this study was a quasi-experiment with a non-equivalent control group design. A total of 50 samples were selected using the proportionate stratified random sampling technique. This study used the Short Version of the New Brief Job Stress Questionnaire (SV-NBJSQ) to measure work stress symptoms in employees. Data was analyzed using the McNemar test because the data were not normally distributed, as shown by the normality test result with a significance value of